Improved mechanical properties of basalt and glass fibre reinforced polymer composite by Incorporating nano silica / Mohamad Asrofi Muslim ... [et al.] - Muslim, Mohamad Asrofi; Jumahat, Aidah; Abdullah, Shahrul Azam; Md Yusof, Fauziah; Zahari, M.Z.; Chalid, Mochamad; Jaafar, Mohd Azrul; Siew Teng Loy, Raymond (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Granite waste that increasingly accumulates yearly is significant with granite industry growth. This research aims to use nano silica extracted from granite dust to identify the effect of nano silica on the mechanical properties of Basalt and Glass Fibre Reinforced Polymer Composite. The approach encompassed three distinct weight percentages of nano silica, specifically 1 wt%, 3 wt%, and 5 wt%, seamlessly blended into a polyester resin matrix. The evaluation of composite mechanical attributes was conducted through compression and Izod impact tests by following ASTM D3410 and ASTM D256. Remarkably, the pinnacle of this enhancement materialises at the 1 wt% threshold,signifying the impact strength and compression strength values. Beyond this point, a decline was observed, underscoring the critical importance of judicious weight percentage selection. This novel composite configuration holds promising implications, particularly for components within container trucks, where the fusion of exceptional impact and compression strength is paramount.